2010
DOI: 10.4314/ijhr.v1i3.55362
|View full text |Cite
|
Sign up to set email alerts
|

Possible nitric oxide modulation in the protective effect of trazodone against sleep deprivation-induced anxiety like behavior and oxidative damage in mice

Abstract: an online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Réus and colleagues (2010) recently showed that imipramine also presents antioxidant properties, reducing oxidative damage and increasing superoxide dismutase and catalase activity in the rat brain. Additionally, imipramine (10 and 20 mg/kg) restored depleted reduced glutathione levels and catalase activity and attenuated raised lipid peroxidation and nitrite concentrations in sleep-deprived mice compared to untreated sleep-deprived mice (Kumar and Garg 2009). Thus, the effects of imipramine in preventing the changes in the behavioral tasks observed in H-BCAA rats might be also associated with its capability to maintain pro-/anti-oxidative homeostasis.…”
Section: Discussionmentioning
confidence: 94%
“…Réus and colleagues (2010) recently showed that imipramine also presents antioxidant properties, reducing oxidative damage and increasing superoxide dismutase and catalase activity in the rat brain. Additionally, imipramine (10 and 20 mg/kg) restored depleted reduced glutathione levels and catalase activity and attenuated raised lipid peroxidation and nitrite concentrations in sleep-deprived mice compared to untreated sleep-deprived mice (Kumar and Garg 2009). Thus, the effects of imipramine in preventing the changes in the behavioral tasks observed in H-BCAA rats might be also associated with its capability to maintain pro-/anti-oxidative homeostasis.…”
Section: Discussionmentioning
confidence: 94%
“…Antioxidants, such as N-acetyl-cysteine, compounds that mimic GPX activity, and zinc exhibit antidepressive effects [156]. In a recent study, Kumar and Garg [157] demonstrated the efficacy of trazodone and imipramine in the treatment of sleep deprivation-induced anxiety-like behavior and oxidative damage in mice, through the restoration of reduced glutathione levels, catalase activity and attenuation of raised lipid peroxidation and nitrite concentrations as compared to untreated sleep-deprived animals.…”
Section: Mood and Psychiatric Disorders And Os-targeting Approachesmentioning
confidence: 99%
“…The apparatus was placed in a darkened, light and sound attenuated and ventilated testing room [6,7].…”
Section: Measurement Of Spontaneous Motor Activitymentioning
confidence: 99%